Impact of a nutrition education intervention on nutrition-related self-efficacy and locus of control among women in Lesotho - Mamotsamai Ranneileng; Mariette Nel; Corinna May Walsh (Frontiers Media S.A., 2023)
IntroductionLesotho is one of the poorest countries in the world with high levels of food insecurity and malnutrition. The aim was to evaluate the impact of a nutrition education intervention informed by self-efficacy and locus of control theories among women in Lesotho.MethodsA randomized pre-test-post-test design was adopted to implement a systematically designed nutrition education intervention in women from Maseru and Berea districts in Lesotho. Women from selected villages were randomly assigned to comparison and intervention groups. Baseline and post assessments were conducted before, and 6 months after the intervention. Nutrition-related self-efficacy and locus of control were assessed using a semi-structured knowledge, attitudes, beliefs, and practices (KABP) questionnaire.ResultsAt baseline, 444 women aged 19-60 years were included. After the intervention, 259 women in the comparison (n = 105) and intervention groups (n = 154) were interviewed. Self-efficacy beliefs that improved significantly in the intervention group but not in the comparison group included increased confidence that they could eat a healthy diet every day [95% CI for the percentage difference (61.5; 76.7)]; an improved ability to secure several healthy foods in the home; increased confidence in engaging in physical activity [95% CI (29.5; 46.6)]; reducing the amount of salt they used in food [95% CI (2.1; 14.0)]; and compiling a budget for food purchases [95% CI (56.1; 72.1)]. Regarding locus of control, the belief in a personal capacity to take charge of one's health through the production and consumption of healthy food improved in the intervention group [95% CI (12.4; 25.0)] but not in the comparison group [95% CI (15.9; 0.4)]. At follow-up, a significantly larger percentage of participants in the intervention group also believed that they could take control of their health and that they could prevent some illnesses by the food they eat.ConclusionA nutrition education intervention that is systematically planned and framed on selected theories of health behavior improved nutrition-related beliefs in self-efficacy and locus of control.